The Design, Development and Evaluation of an Array-Based FES System with Automated Setup for the Correction of Drop Foot. Issue 20 (2015) - Kenney, Laurence P.; Heller, Ben W.; Barker, Anthony T.; Reeves, Mark L.; Healey, T. Jamie; Good, Timothy R.; Cooper, Glen; Sha, Ning; Prenton, Sarah; Howard, David
Abstract: Functional electrical stimulation has been shown to be a safe and effective means of correcting drop foot of central neurological origin. However, despite recent technological advances, the set-up of surface stimulators remains a challenge for many users with drop foot. The automation of the setup process through the use of electrode arrays has been proposed as a way to address this problem. This paper describes a series of research and clinical studies which have led to the first demonstration of unsupervised automated setup of an electrode-array based drop foot stimulator. Finally, future research plans are discussed.